The Impact of Fasting on Student's Academic Performance - Arni Arni; Rusdiana Husaini; Muqarramah Sulaiman Kurdi; Musyarrafah Sulaiman Kurdi (CV. ALIM'SPUBLISHING, 2024)
This research explores the impact of Ramadan fasting on student's academic performance and identifies socio-cultural factors and interventions that can mitigate any negative effects. The study investigates three research questions: (1) the impact of fasting on children's cognitive abilities and academic performance, (2) socio-cultural factors influencing the relationship between fasting and academic achievement, and (3) specific strategies or interventions to support fasting children's academic success during Ramadan. A literature review was conducted to examine previous research on the topic, incorporating studies that explored the physiological, psychological, and socio-cultural dimensions of Ramadan fasting among children. The findings highlight the complex relationship between fasting and academic performance, with studies reporting varying effects ranging from negative to neutral or even positive. Socio-cultural factors such as family support, cultural attitudes towards education, dietary habits, school policies, and socio-economic status were identified as influential factors shaping children's experiences during fasting and their academic outcomes. Additionally, several strategies and interventions were identified to mitigate the negative effects of fasting on academic performance, including nutritional guidance, hydration strategies, flexible school policies, supportive school cultures, family involvement, peer support networks, time management skills, emotional well-being support, physical activity opportunities, and continued academic support. These findings underscore the importance of holistic approaches to support fasting children's academic success during Ramadan, addressing their physical, emotional, social, and academic needs.